Exploring Life Orientation Teachers’ Experiences Facilitating Active and Self-directed Learning in Cooperative Learning Classrooms - Seherrie, Aloysius Claudian (Studies in Learning and Teaching, 2026)
Cooperative learning is a vital pedagogical method in teacher education, enabling teachers to facilitate active and self-directed learning in authentic contexts. This paper, exploring life orientation teachers’ experiences facilitating active and self-directed learning in a cooperative learning classroom, followed a qualitative interpretive-phenomenological design. Through purposive sampling, seven participants were selected based on their experience in facilitating active and self-directed learning. Data were collected through interviews and analyzed using inductive thematic analysis. Cooperative learning emerged as a pivotal support strategy to enhance active and self-directed learning skills, facilitated by teachers who are crucial to promoting these skills and equipping learners with 21st-century life skills. Implementing active and self-directed learning practices through a cooperative learning approach should begin with teacher education. Therefore, policy and a skills-driven cooperative approach must be implemented to promote active and self-directed learning. Further research is needed, using a larger sample, which might yield different or more nuanced results in cooperative learning classrooms.